Impacts of Adapted Altitude on Yield and Some Others Characteristics of Bituminaria bituminosa - Zeki Acar; İlknur Ayan; Mehmet Can; Gülcan Kaymak (Turkish Journal of Agriculture: Food Science and Technology)
This study was carried out with 86 Bituminaria bituminosa (Bitbit) genotypes collected from Central Black Sea Region of Northern Anatolia in Samsun in 2012. After cleaning, seeds scarifying with sandpaper and sown in small pots. In November of 2012, the seedlings were transplanted to experimental field. No fertilizer and water applied throughout the study and spring and autumn elongation, hay yield and harvesting number in the second year of the plants (2014) were observed during the study. According to correlation analysis, there was a negative and statistically significant linear correlation between altitude and spring elongation, autumn elongation, harvest number. There was also a negative statistically insignificant correlation between altitude and hay yield. A positive and significant correlation was found between hay yield and spring and autumn elongations, harvest number; between spring and autumn elongations and number of harvest. Some genotypes taken from high altitudes stayed dormant in winter period, furthermore they started elongation later than the others and a slight growth was recorded in autumn. In the light of these results, it is possible to improve cultivars for different ecological conditions.